Evaluation of modified petroff’s method and manual MGIT culture system to facilitate detection of acid-fast bacilli in smear-negative presumptive cases of pulmonary tuberculosis - Jamali, Sana; ., Richa; Srivastava, Vinod K (Indian Journal of Community Health, 2019)
Background: Tuberculosis is a major public health problem in India. According to RNTCP guidelines, all efforts are to be made to diagnose tuberculosis on the basis of detection of AFB/ MTB in the clinical specimen; hence all those cases where AFB/ MTB have not been detected are presumptive cases of tuberculosis. In this background, the present study aims to detect AFB/ MTB in the sputum of clinico-radiologically presumptive cases of pulmonary tuberculosis using direct ZN microscopy, Modified Petroff’s method followed by ZN microscopy & MGIT liquid culture method. Materials and Methods: A total of 94 sputum samples which were negative for AFB by direct ZN microscopy at the DMC of the institute, were subjected to Modified Petroff’s method followed by microscopy & MGIT liquid culture test to find out any additional yield of bacteriologically confirmed disease. Result: Out of 94 specimens, 20 (21.28%) were positive for AFB on ZN microscopy post Modified Petroff’s method. Among all the specimens, 30 (31.91%) were found to be positive by MGIT liquid culture method with average time to detection growth (TTD) around 16.73 days (2-38 days). Conclusion: Modified Petroff’s method followed by ZN microscopy & MGIT test for mycobacterial culture can improve case detection.